Histopathological features of ovarian mass among patients attending a tertiary care hospital in South India - Kasiraj, Radhika; Logeswari, B. M.; Banupriya, P.; Amirtha, C.; Veena, R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: First of all, globally, ovarian tumors are becoming a more common source of morbidity and death. The goal of the current investigation was to ascertain the incidence of different ovarian tumor histological and morphological variants in a tertiary healthcare center in southern India. Methods: The study, which took place in a tertiary healthcare facility in Chennai, involved 89 ovary specimens that were obtained over the course of 18 months (from August 2021 to December 2022) from patients in the obstetrics and gynecology department. The specimens underwent both histological and critical gross examination. Standard H&E-stained paraffin slices were observed. After being organized on proforma, the histology results were examined. Results: A total of 89 patients, ranging in age from 16 to 90, were enrolled in the study. The majority of patients (30.3%) were in the age range of 31 to 40 years. The majority of ovarian tumors were benign, accounting for 58 (65.2%) of the total, while malignant tumors accounted for 25 (28.1%). The most prevalent type of tumors, according to the World Health Organization (WHO) classification, were surface epithelial tumors (76.12%), followed by germ cell tumors (18.46%). In the current investigation, one case of metastatic tumors to the ovaries was also identified. Serous cystadenoma 29 (32.6%) was found to be the most prevalent subtype among the many known subtypes of ovarian tumors, followed by papillary serous carcinoma 14 (15.7%). Conclusions: Compared to malignant or borderline tumors, benign ovarian tumors are more common. Surface epithelial tumors are the most prevalent histological subtype of ovarian cancers, followed by germ cell tumors. It’s critical to distinguish between benign and malignant tumors in order to ensure appropriate treatment and healing. Future research of this kind with a larger sample size is advised.